2018
DOI: 10.1002/app.46453
|View full text |Cite
|
Sign up to set email alerts
|

Positive temperature coefficient effect and mechanism of compatible LLDPE/HDPE composites doping conductive graphite powders

Abstract: Linear low density polyethylene (LLDPE)/high density polyethylene (HDPE) blends doped conductive graphite powders were constructed by the traditional melt‐blending method to acquire the conductive compatible polymer composites, and corresponding positive temperature coefficient (PTC) effect of electrical resistivity was investigated. The results indicated that the room‐temperature resistivity gradually decreased and PTC effects were remarkably enhanced by regulating the graphite contents or LLDPE/HDPE ratios. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…However, when the measurements were conducted for the second run at 40 and 30 °C consecutively after the elevated temperature (100 °C) run, the dielectric losses were found to increase again at approximately the same level as for the first run. Accordingly, the main contribution of the lowering of the dielectric losses was found to be linked to the thermal expansion of the composite for which the increase of temperature (50 to 100 °C) causes a slight separation of previously connected particles 14, [39][40][41][42] .…”
Section: Effect Of Temperature On the Electrical Responsesmentioning
confidence: 99%
“…However, when the measurements were conducted for the second run at 40 and 30 °C consecutively after the elevated temperature (100 °C) run, the dielectric losses were found to increase again at approximately the same level as for the first run. Accordingly, the main contribution of the lowering of the dielectric losses was found to be linked to the thermal expansion of the composite for which the increase of temperature (50 to 100 °C) causes a slight separation of previously connected particles 14, [39][40][41][42] .…”
Section: Effect Of Temperature On the Electrical Responsesmentioning
confidence: 99%
“…Based on this principle, CPCs can be designed into various promising sensors, including strain sensor, [57,[69][70][71][72][73][74][75][76][77][78][79] pressure sensor, [80][81][82][83][84][85][86][87][88][89][90][91] temperature sensor, [92][93][94][95][96][97][98][99][100][101][102][103][104] and solvent sensor, [19,[105][106][107][108][109][110][111][112][113][114] to monitor the external stimuli, such as strain, pressure, temperature, solvent, and so on. Until now, there are already some published review articles, [115]…”
Section: Introductionmentioning
confidence: 99%
“…Polymer blending influences PTC properties in three ways. First, some researchers found that different polymer matrix with different polymer crystallization behavior can exhibit different thermal volume expansion behavior and thus influence PTC behavior [24][25][26]. Luo et al [25] found that ethyl vinyl acetate (EVA)/LDPE/CB have lower PTC intensity and lower temperature at the maximum of resistivity exists than LDPE/CB, which is believed to be the result of imperfection of crystalline regions between EVA and LDPE.…”
Section: Introductionmentioning
confidence: 99%